The activities of Israel as a service organization of the National Police - Юринець, Юлія Леонідівна; Добчис, Ярослав Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Peculiarities of the National Police of Israel, which (activities) aimed mainly at implementing service functions to the public. We study the historical background of this kind of activity, the theoretical foundations of the activities and structure of the Israel National Police in connection with the implementation of service functionsEmphasis is on the critical experience of Israel’s National Police for Ukraine as both countries faced similar challenges: the need for building a modern democratic state in an aggressive terrorist activity powerful neighbor. The attention that the overwhelming focus of the National Police of Israel to Ukraine to provide services to citizens and society lies historically and due to the fact that the Israeli police was the forerunner organization "and Hashomer" and the next - and the "police of Jewish settlements" that asked for the protection of Jewish settlements and Jewish settlements from the aggressive actions of the Arabs.Embodiment service nature of the Israeli National Police have a close relationship with the public, focus on the needs of society, including the fight against corruption and economic crimes in power, focus on vulnerable populations, including children and youth, attention to the search of missing people and stolen cars, careful consideration of complaints population objective guarantees complaints concerning police activities, such informal consideration of special courts and more.Service nature of the National Police of Israel provided the features of the structure of the police, which is as close to the population, such as regional centers Police (MPS), which are located mainly in remote areas in the Arab settlements in areas of new immigrants in rural areas, in tourist areas and beaches, that is, in places that need monitoring and intervention more often than elsewhere.The detailed structure of the Israeli National Police, made the scheme of interaction of individual regional and specialized units.The purpose of the police, according to Art. 3 Order of Police (as amended in 1971), defined: prevent offense; investigation of offenses and expression; wanted criminals and bringing them to justice; control and monitoring of road traffic; public order and security of life and property; reliable protection of prisoners and detainees; responsible for internal security.